A leitura de literatura na escola: por uma educação emocional de crianças na educação infantil - Silva, Nívea Priscilla Olinto da (2010)
This dissertation examines the contributions of juvenile literature reading for the problematization of the emotional experiences and conflicts of children at infant education. Its importance consists in providing useful information for the pedagogic work orientated to literature reading at the initial series of basic education, in order to increase the teacher s ability to explore the literary text from its instigating and enriching nature in view of the child s emotional experiences and conflicts. It is methodologically based on the principles of the qualitative research, what characterizes it as a case study. The research focused a level V-infant education class with 28 students in 5-6 age group, at a public school of Natal, State of Rio Grande do Norte (Brazil). The used resources were: audio recording, field diary, and interviews. Seventeen classes were carried out and they consisted in reading sessions of classic and contemporaneous tales, fables, and legends which used different didactic strategies. These sessions were developed in accordance with the reading experience through scaffolding instructions as it was described by Graves & Graves. The theoretical references were the studies of Amarilha (1997/ 2006), Bettelheim (2004), Coelho (1987/2000), Damásio (2005), Del Nero (2003), Eco (1994/2006), Held (1980), Iser (1996), Jauss (2002), Stierle (2002), Wallon (2007), Telles (2006), Yunes (2003), and Zilberman (1987). The analyses showed that literary reading in class is a special environment for inclusion of the reader s subjectivity; as well as the inclusion of their emotional experiences and their conflicts within the story by way of helping children think and become suitable for dealing with their inner feelings. The literary reading is presented as an experiential and formative activity which helps children understand their emotions through a process of identification, exteriorization, and catharsis; what implies that the esthetic experience from the text makes possible the reader s self-knowledge and increases the perception of his inner feelings and objective reality so that this reader has emotional capital to deal with life difficulties. It is important to highlight that the discussions carried out in the class represented a field of sharing experiences through which each reader had the chance to present their experience of life to the others, including their sorrows and sufferings, in order to help them to develop best strategies to deal with the social environment